Alternative approaches to conventional antiepileptic drugs in the management of paediatric epilepsy. Issue 11 (20th October 2006) - Kneen, R; Appleton, R E
Abstract : Over the last two decades, there has been a rapid expansion in the number and types of available antiepileptic drugs (AEDs), but there is increasing concern amongst parents and carers about their unwanted side effects. Seizure control is achieved in approximately 75% of children treated with conventional AEDs, but non-conventional (or non-standard) medical treatments, surgical procedures, dietary approaches, and other non-pharmacological treatment approaches may have a role to play in those with intractable seizures or AED toxicity. Many of the approaches are largely common sense and are already incorporated into our current practice, including, for example, avoidance techniques and lifestyle advice, while others require further investigation or appear to be impractical in children.